The role of general motor skills in talent identification: A systematic review - Sliedrecht, F.; Schoof, S.; Hartman, E. (International Journal of Sports Science & Coaching, 2025)
Successful talent identification increases the chances of sporting and financial success since it provides talented children and adolescents with the most optimal learning environment to realize their potential. Hence, coaches and clubs of many sport disciplines are eager to identify talented athletes. General motor skills are often incorporated in talented identification research, as it is considered fundamental to learning sport-specific motor skills. This systematic review aimed to examine to what extent general motor skills can contribute to the identification of talented athletes aged six to eighteen. Five electronic databases were searched, which resulted in 22 eligible studies (13 cross-sectional and 9 longitudinal studies). Quality assessment was done using the Quality Assessment with Diverse Studies tool. The vast majority of both cross-sectional and longitudinal studies found either differences in general motor skills in favour of the talented athletes (59% of the studies) or no differences between talented athletes and their peers (36% of the studies). These results show that assessing general motor skills could contribute to talent identification programs, but caution should be paid prior to the implementation of these general motor skill test batteries due to the inconclusive nature of the findings. Hence, there is a need for future high-quality longitudinal studies which are recommended to conduct sex- and age-specific analyses, address the existing gap in the literature by including athletes from diverse sports beyond football, and investigate whether assessing manipulative skills and capturing movement quality could be a valuable addition to assessing locomotor skills for identifying athletic talent.